Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was doing some problems for Olympiad training and encountered this: How would you prove that

$(a+b+c+d)-(a+c)(b+d)\geq 1$?

We are told that $0<a,b,c,d<1$ and the product $abcd=(1-a)(1-b)(1-c)(1-d)$.


share|cite|improve this question
Tough indeed, try $a=b=c=d=1$. – Did Oct 30 '11 at 17:01
Sorry restriction given is that a,b,c,d are between 0 and 1. And that $abcd=(1-a)(1-b(1-c)(1-d)$ – Henry Pan Oct 30 '11 at 17:13
@HenryPan Out of curiosity, from where was this taken? – mathmath8128 Oct 30 '11 at 17:49
Next question: interpret this probabilistically. – Michael Hardy Oct 30 '11 at 17:54
Me and my friend were in an advanced math class and he gave it to us. I belies it's froma book – Henry Pan Oct 30 '11 at 18:04

let $x = a+c$, $y=b+d$, you have to prove

$x+y - xy \geq 1$

$(x-1)(y-1) \leq 0$

Suppose this is false, then $x-1$ and $y-1$ are both positive or both negative. But:

$x-1 > 0$ and $y-1 > 0$


$a+c > 1$ and $b+d > 1$


$a >1-c$ and $c > 1-a$ and $b> 1-d$ and $d > 1-b$

Multiplying them all you get contradiction with assumption $abcd=(1-a)(1-b)(1-c)(1-d)$. Same argument when they are both negative.

share|cite|improve this answer

Write $abcd = (1-a)(1-b)(1-c)(1-d)$ as $\frac{abc}{(1-a)(1-b)(1-c)} = \frac{1-d}{d}$ and solve for $d$: $$d = \frac{(1-a)(1-b)(1-c)}{(1-a)(1-b)(1-c) + abc}$$ Note that the denominator is positive under the given conditions on $a,b,c$. Now substitute that in to $F = a + b + c + d - (a+b)(c+d) - 1$ and put over the common denominator $(1-a)(1-b)(1-c) + abc$. It looks messy, but the numerator must be a polynomial in $a,b,c,d$ of total degree at most 4, and it is 0 when $b=0$ or $b=1$ or $a+c=1$. It turns out that we get $$F = \frac{b(1-b)(a+c-1)^2}{(1-a)(1-b)(1-c) + abc} \ge 0$$

share|cite|improve this answer

$$abcd=(1-a)(1-b)(1-c)(1-d) \Rightarrow (a+c+b+d) +abc+abd+acd+bcd =1+ab+ac+ad+bc+bd+cd$$

So you need to prove that

$$1+ ab+ac+ad+bc+bd+cd-abc-abd-acd-bcd \geq 1+ab+ad+bc+bd $$


$$ac+bd \geq abc+abd+acd +bcd \,.$$

This seems simpler, but still not obvious. The problem is reduced to:

$$abcd=(1-a)(1-b)(1-c)(1-d) \Rightarrow ac+bd \geq abc+abd+acd +bcd$$

with the extra restriction $0< a,b,c,d <1$.

Lagrange multipliers should solve it, but there is probably a much simpler solution

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.